Serological frequency of Ehrlichia canis in canines suspected of ehrlichiosis in the northern districts of Lima, Peru - Cusicanqui S, Juan (2020)
The study aimed to determine the serological frequency of Ehrlichia canis in canine patients in the northern area of ​​Metropolitan Lima, Peru. Data was obtained from a clinical analysis laboratory, which receives samples from veterinary clinics of the area. Records with analyses against E. canis during the 2014-2016 period were taken, as well as those with blood count analysis. The samples were analysed with a commercial kit specific for E. canis. The serological frequency of E. canis and the association between the serological results with the variables sex, age and breed type were evaluated. A frequency of 59.4% (723/1216) of ehrlichiosis positive canines was found. A significant association of ehrlichiosis was found for patients older than 2 years and for crossbreds. In adult dogs, those positive for the disease have lower values of the red, white and platelet series compared to negative dogs.